Fenomena Alih Kode dan Campur Kode dalam Interaksi Keluarga Melalui Konten TikTok Metha Armelita - Septiani, Alika Dwi; Maheltra, Alma Neysa; Heryanti, Denia; Adawiyah, Sulis Najahul; Suherman, Syahira Mawla; Lisnawati, Iis (Innovative: Journal Of Social Science Research, 2025)
This study analyzes the phenomenon of code-switching and code-mixing in family interactions displayed through Metha Armelita's TikTok content. In the context of urban Indonesian society, especially the young generation of South Jakarta, code-switching and code-mixing become linguistic strategies that reflect social identity, cultural affiliation, and bilingual cognitive processing. This research uses a descriptive qualitative and psycholinguistic approach with a case study on one TikTok video featuring a conversation between a mother and daughter. The analysis showed that the use of English terms such as burnout, overwhelmed, and panic attack reflected an emotionally salient lexicon that was easily accessible to young speakers. In contrast, the mother responds with the local language (Javanese) which indicates emotional attachment to the L1 and decoding failure due to the linguistic gap. Code-mixing also serves as a symbol of urban lifestyle and identity expression, while code-switching on the mother's part reflects an attempt to maintain clarity of communication. This study highlights the cross-generational linguistic dynamics in the digital era and the importance of psycholinguistic understanding in bilingual family interactions.